(NoBRATNOE RASSEQNIE BYSTRYH IONOW (B:s (NtEORIQ(B, (N\KSPERIMENT(B, (NPRAKTIKA (B/s - (N{IPATOW(B, (N|DUARD tRIFONOWI^s; (NwEDRINSKIJ(B, (Nr(B.(Nw(B.s ((NrOSTOW(B-(NNA(B-(NdONU (B:s (NiZD(B-(NWO rOST(B. (NUN(B-(NTA(B,s, 1988)
(NuKAZ(B. (NIMEN(B. (NI PREDM(B.: (NS(B. 149-152s
(NbIBLIOGR(B.: (NS(B. 139-147s
Keywords: (NfIZI^ESKOE STROENIE MATERIIs